Bibliometric analysis: Learning outcomes research in mathematics learning (1992-2023) - Muhammad, Ilham; Marchy, Febrinna; Elmawati, Elmawati; Samosir, Christina Monika (UNIVERSITAS NEGERI MALANG, 2023)
Learning Outcomes are values, attitudes and skills as a result of the learning process. The purpose of this study is to look at the research landscape related to learning outcomes in mathematics learning from 1992 to 2023. The method used is descriptive bibliometric analysis. The data taken comes from the enhanced Scopus database. The results showed that the trend of the most publications related to learning outcomes in learning mathematics was in 2020 and 2022 with a total of 14 publications. The most citation trend occurred in the 2009 publication which has been cited 262 times. The country that has had a major impact on research on learning outcomes in mathematics learning is the United States of America. The research focus is divided into three parts, namely, 1) motivation and reasoning; 2) , technology and higher school; 3) universities and assessments. New themes in this field are mathematical problems, higher education, blended learning and geogebra. The learning outcomes keyword is not directly connected with the 7 other keywords, namely, ict, critical thinking, mathematics achievement, pre service teacher, gender different, secondary school. Keywords with new themes such as mathematical problems are not together with learning outcomes but are not directly connected with keywords with other new themes such as higher education, blended learning and geogebra